Gelassenheit - Heidegger, Martin 1889-1976 (Pfullingen Neske, 1959)
The book contains two texts:- 'Gelassenheit' The speech was given at the celebration of the 175th birthday of composer Conradin Kreutzer on October 30, 1955 in Messkirch.- 'Zur Erörterung der Gelassenheit' - From a country road conversation about thinking: Taken from a conversation written in 1944/45 between a researcher, a scholar and a teacher.
Keywords: 20th Century (1901-2000); Philosophy; Germany